Responsive versus Scheduled Interval Feeding for Preterm and Low Birth Weight Infants: A Systematic Review - Nurul Purnamasari; Ririn Azhari (The International Journal of Medical Science and Health Research, 2025)
Introduction: Optimal feeding for preterm and low birth weight (LBW) infants is critical for growth and development, yet the ideal feeding strategy remains debated. This systematic review evaluates the effects of responsive (cue-based) feeding compared with traditional scheduled interval feeding on a comprehensive range of outcomes in this vulnerable population. Methods: Following PRISMA guidelines, we conducted a systematic search of CENTRAL, MEDLINE, EMBASE, and CINAHL for randomized controlled trials (RCTs) comparing responsive versus scheduled feeding in preterm (<37 weeks' gestation) or LBW (<2500 g) infants. Two reviewers independently performed study selection, data extraction, and risk of bias assessment using the Cochrane RoB 2 tool. Data were synthesized using random-effects meta-analysis for homogeneous outcomes, with results reported as mean difference (MD) or risk ratio (RR) with 95% confidence intervals (CI). A narrative synthesis was performed for heterogeneous data. The certainty of evidence was assessed using the GRADE framework. Results: Nine RCTs involving over 650 infants were included. Meta-analysis revealed that responsive feeding resulted in a slower rate of weight gain compared to scheduled feeding (MD −1.36 g/kg/day, 95% CI −2.44 to −0.29; low certainty) but significantly reduced the time to achieve full oral feeding (MD −5.53 days, 95% CI −6.80 to −4.25; low certainty). There was no consistent or statistically significant effect on the overall duration of hospital admission (MD −1.42 days, 95% CI −5.43 to 2.59; very low certainty). Data on critical outcomes, including long-term neurodevelopment, parental satisfaction, breastfeeding duration, and specific adverse events like necrotizing enterocolitis, were systematically absent across the included trials. Most included studies were small and possessed methodological limitations, primarily a high risk of bias due to lack of blinding. Discussion: The evidence highlights a central clinical trade-off: responsive feeding appears to accelerate the acquisition of oral feeding skills at the potential cost of slower short-term weight gain. The lack of a corresponding reduction in hospital stay suggests that other discharge criteria, such as achieving a specific weight, may negate the benefits of earlier feeding proficiency. A profound misalignment exists between the developmental philosophy of responsive feeding and the predominantly biomedical outcomes measured in existing trials. Conclusion: The current evidence, which is of low to very low certainty, is insufficient to recommend the universal adoption of responsive feeding over scheduled feeding to improve growth or shorten hospitalization for preterm and LBW infants. Responsive feeding appears to be a safe alternative that may hasten the transition to full oral feeding. High-quality, large-scale RCTs that measure patient- and family-centered outcomes are urgently needed.